Dose-effect study of the serotonin agonist R-8-OH-DPAT on opioid-induced respiratory depression in blesbok (Damaliscus pygargus philipsi) and impala (Aepyceros melampus). (November 2019) - Pfitzer, Silke; Laubscher, Liesel; Meyer, Leith; Warren, Kristin; Vaughan-Higgins, Rebecca; Raath, Jacobus P.; Laurence, Michael
Abstract: Objective: To determine whether the R-enantiomer of 8-hydroxy-2-(di-n-propylamino) tetralin (R-8-OH-DPAT) alleviates respiratory depression in antelope species immobilized with etorphine. The experiment also aimed to establish the most clinically effective dose of this serotonin 5- HT1A receptor agonist. Animals: A group of six female blesbok and six female impala. Study design: Each animal was subjected to four immobilization treatments in a prospective four-way crossover design—control treatment consisting of only etorphine at 0.09 mg kg –1 and three treatments consisting of etorphine at 0.09 mg kg –1 combined with 0.005, 0.02 and 0.07 mg kg –1 of R-8-OH-DPAT, respectively. Induction, quality of immobilization and recovery were monitored in each treatment. Physiological variables including heart rate, respiratory rate, arterial blood pressure and blood gases were measured for 35 minutes during immobilization. A linear mixed model was used to assess the effects of treatments over the recumbency period. Results: R-8-OH-DPAT did not influence induction, immobilization or recovery scores. Respiratory rate in blesbok was increased in the medium- and high-dosage R-8-OH-DPAT treatment group. However, this increased respiratory rate did not translate into improvements of arterial partial pressure of oxygen (PaO2 ) values in the blesbok. The medium and higher dosages of R-8-OH-DPAT in impala led to an improved PaO2 as well as to decreased opioid-induced tachycardia during the first 10 minutes of immobilization. Conclusions and clinical relevance: Previous reports indicated that the racemic mixture of 8-OH-DPAT injected intravenously had a positive effect on blood-gas values in etorphine-treated hypoxemic goats. In this experiment, similar effects could be seen in impala at the higher dosage rates of R-8-OH-DPAT. However, failure to achieve an improvement of blood-gas values in blesbok was an unexpected result. It could be speculated that the dosage, species-specific differences of serotonin receptors or the use of the R-enantiomer of 8-OH-DPAT might play a role.